ANALISIS KOMPONEN PARIWISATA DAN ZONASI KAWASAN PARIWISATA MELALUI TEORI TRIPARTITE DI KAWASAN WISATA PANTAI KEDONGANAN - Angelina Hartono; Gde Made Nugraha Regita; Nyoman Wibawa Saputra; Ni Wayan Mita Damayanti; I Made Trisna Semara; Ayu Arun Suwi Arianty; Gusti Ayu Eka Suwintari (Bajang Institute, 2024)
This study aims to analyze the tourism components of Kedonganan Village based on the 4A model (Attraction, Amenities, Ancillary, Accessibility) and Community Involvement and evaluate the suitability of tourism area zoning using the Tripartite concept (Core Zone, Buffer Zone, and Service Zone). This research uses qualitative methods with purposive techniques in determining informants, and data is collected through interviews, observation, and documentation. The result showed that Kedonganan Village has the potential for natural and culinary tourism with the active role of the local community, but the application of zoning is not fully in accordance with the guidelines of the Tripartite concept. This research provides recommendations for zoning improvements to be more sustainable and adaptive to environmental changes